Carer involvement with drug services: a qualitative study. (6th December 2012) - Orr, Linda C.; Barbour, Rosaline S.; Elliott, Lawrie
Abstract Background Empirical research suggests that involving carers brings benefits to families and services. Consequently, drug‐related policy and guidance has increasingly encouraged drug services to involve carers at all levels of service provision. Objective To explore the purpose and scope of carer involvement with adult drug services in North‐east Scotland. Design, Setting and Participants A total of 82 participants (20 informal carers, 43 service providers and 19 policy makers) were purposively selected to take part in a qualitative study. Eight focus groups and 32 interviews were conducted between 2007 and 2008. Findings Three themes were identified through thematic coding: 'Current levels of involvement', 'Use of the term carer' and 'Opportunities for change?' Carer involvement was described as limited, unplanned and unstructured, and consisted largely of information and advice, practical and emotional support, and signposting of services. Although use of the term 'carer' was contested within and across the groups, caring in a drug context was considered the 'same but different' from caring in other contexts. Carers remained sceptical that services actually wanted to involve them in supporting their relative or to offer carers support in their own right. Many service providers and policy makers regarded carer involvement as an aspiration. Conclusion Encouraging carers, service providers and policy makers to reach a shared understanding of caring in a drug context may help translation of policy into practice. However, there is also a fundamental need for drug services to widen the level and type of involvement activities on offer to carers.